Kepastian Hukum Sertifikat Hak Milik atas Tanah Dalam Hukum Pertanahan Indonesia - Helena Sumiati; Andriansah; Bagio Kadaryanto (Universitas Merdeka Madiun, 2021)
Article 3 letter a Government Regulation Number 24 of 1997 concerning Land Registration says to provide legal certainty and legal protection to rights holders of land parcels, apartment units and other registered rights so that they can easily prove themselves as holders of the rights concerned. . However, in the course of time, the existence of this Registration Regulation is considered to have not been optimal because there are several obstacles including limited funds and personnel so that control of land is largely not supported by adequate evidence. In addition, this Government Regulation is not sufficient to provide the possibility for the implementation of land registration in a short time and with satisfactory results. The type of research used in the writing of this research is Normative legal research, which discusses the legal certainty of land title certificates in Indonesian land law. From the results of the research, it can be concluded that the legal certainty of land title certificates is not in accordance with legal certainty regarding the object of land rights, the subject of land rights and regarding certainty over land and with this state guarantee given to the owner or certificate holder it can be given because the land is already registered. in the state land administration system. Ideally, land ownership in order to have appropriate legal certainty is protection for land rights holders which are legally formal rights for every Indonesian citizen, however actions to take action against any party who occupies land by certain parties illegally must be carried out with care. -be careful not to cause social conflict or conflict between citizens and the government.